Simultaneous Interpretation of Religious Quotes Used in Selected Speeches by Barack Obama - Reem Rostom; Mekhala Venkatesh (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2023)
Simultaneous interpretation is a common style of translation used in media, especially in political events. It requires training, experience, and mastery of various skills, including listening, comprehension, retrieving, reformulating, and creating accurate translations. The paper analyzes English transcripts of original texts and Arabic transcripts of interpreted texts, broadcast live on Arabic TV channels. The paper focuses on two speeches by former US President Barack Obama. The objective of utilising religious terms in most political texts is not to deliver a religious message, but rather to create a rhetorical and pragmatic plan that leaves a pleasant impression in the minds of the audience. The examples of the simultaneous interpretation of utterances with embedded messages in political discourse illustrate that implicatures, which do not convey a corresponding message to listeners of interpreted texts similar to that transmitted to recipients of original texts, may result in dissimilitude between the impact of the original message and that of the interpreted one. This incompatibility may lead to differences in audiences' attitudes.